As praias entre a Foz do Douro e a Granja : algumas reflexões sobre a erosão costeira - Oliveira, Carla Sofia Freitas de (2014)
Coastal erosion is a phenomenon that should be analyzed at a global scale. The coastal erosion is affecting an important part of the Portuguese coast. The more affected areas are the sandy coastlines (for example, the segment between Espinho and Cape Mondego), and everywhere the substratum is soft (for example, many places to the east of Olhos de Água, in Algarve). Coastal erosion is affecting beaches but also the man made structures (groins, sea walls). This is a relevant problem because beaches play an important role in the economy of the country, specially supporting the coastal tourism industry. Coastal erosion has many and inter-acting causes, so it is important to study them carefully in each context. The coastline between the mouth of the River Douro and the Granja beach is one example of the many areas affected by coastal erosion. In this coastal segment, the beaches lay over a rocky substratum (Iberian massif). Recent human interventions (construction and reinforcement of treated used waters discharger at Canidelo, detached breakwater of Aguda) caused the thinning of the beaches in the south of the structures (Francelos and Granja Beaches). The construction of new River Douro jetties may also affect this coastal segment. Our goal is to analyze the impact of this new structure and other human interventions on studied beaches. We also aim to confront this findings with the wave climate registered by Instituto Hidrogáfico. In order to accomplish these tasks we started, in April 2008, a monitoring of those beaches between Cabedelo and Granja beach. We have registered every month the beach profiles with a differential GPS. We have choose six different places, always departing from the same point and with the same direction. (...)